ЎҚУВЧИЛАРНИНГ ИЖОДКОРЛИК ҚОБИЛИЯТЛАРИНИ РИВОЖЛАНТИРИШНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ - Ҳамдамова, Н.М. (SCIENCE and SOCIETY, 2020)
The article discusses the use of polytechnic education in secondary schools, the development of creative abilities of students in modern production, the pedagogical and psychological features of the organization of creative work of students, the use of the latest achievements of science and technology.It also covers the levels of development of students ’creative abilities, the possibilities of developing students’ creative abilities through the design and construction of various devices.